1991
DOI: 10.1113/expphysiol.1991.sp003495
|View full text |Cite
|
Sign up to set email alerts
|

Okadaic acid, a protein phosphatase inhibitor, increases the calcium transients in isolated ferret ventricular muscle

Abstract: SUMMARYOkadaic acid is a protein phosphatase inhibitor which has been found to produce a marked positive inotropic effect in isolated cardiac muscle. Using aequorin-injected ferret papillary muscles, we demonstrate that the increase in tension seen with okadaic acid is accompanied by a simultaneous increase in the amplitude of the calcium transients. By comparison with the effects of changing the extracellular calcium concentration, it is shown that the increase in calcium transient amplitude can account for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…CaMKII autophosphorylation was only observed when phosphatase 1 was inhibited, but then pacing strongly enhanced autophosphorylation. The increase in CaMKII autophosphorylation is likely due to direct inhibition of phosphatases dephosphorylating CaMKII, but it is also possible that phosphatase inhibition enhances CaMKII activation by increasing [Ca 2+ ] i (via an increase in the phosphorylation level of Ca 2+ -regulatory proteins; [38][39][40] We also show however that in the presence of okadaic acid the RyR Ser-2814 was the first site significantly increased in response to pacing, not global CaMKII Thr-287. This does not rule out that CaMKII specifically associated with the RyR does become significantly transiently activated and/or autophosphorylated sooner, especially when considering that the local [Ca 2+ ] around the RyR in the junctional cleft might reach very high concentrations during each excitation-contraction cycle [41][42][43].…”
Section: Does Pacing Activate Camkii and Increase Autophosphorylation?mentioning
confidence: 81%
“…CaMKII autophosphorylation was only observed when phosphatase 1 was inhibited, but then pacing strongly enhanced autophosphorylation. The increase in CaMKII autophosphorylation is likely due to direct inhibition of phosphatases dephosphorylating CaMKII, but it is also possible that phosphatase inhibition enhances CaMKII activation by increasing [Ca 2+ ] i (via an increase in the phosphorylation level of Ca 2+ -regulatory proteins; [38][39][40] We also show however that in the presence of okadaic acid the RyR Ser-2814 was the first site significantly increased in response to pacing, not global CaMKII Thr-287. This does not rule out that CaMKII specifically associated with the RyR does become significantly transiently activated and/or autophosphorylated sooner, especially when considering that the local [Ca 2+ ] around the RyR in the junctional cleft might reach very high concentrations during each excitation-contraction cycle [41][42][43].…”
Section: Does Pacing Activate Camkii and Increase Autophosphorylation?mentioning
confidence: 81%
“…This effect was accompanied by accelerated relaxation. Under the same conditions, PLB phosphorylation and free intracellular Ca 2+ were enhanced, which could explain the higher contractility [39,40]. Additional evidence for a role of PP1 in the control of cardiac function comes from the observations that PP1 activity is increased [13] and the level and phosphorylation state of I-1 is decreased [41] in human failing hearts.…”
Section: Discussionmentioning
confidence: 91%
“…Therefore, we present here only data on electrically driven papillary muscles. Others have shown that these preparations exhibit changes in intracellular Ca 2ϩ (21) that are increased by PP inhibitors (12). Figure 2 depicts original tracings of single contractions in electrically driven guinea pig papillary muscles at high time resolution.…”
Section: Resultsmentioning
confidence: 99%